Racial Category Usage in Education Research: Examining the Publications from AERA Journals - Dominique J. Baker; Karly S. Ford; Samantha Viano; Marc P. Johnston-Guerrero (SAGE Publishing, 2024)
How scholars name different racial groups has powerful salience for understanding what researchers study. We explored how education researchers used racial terminology in recently published high-profile peer-reviewed studies. Our sample included 1,427 original empirical studies published in the nonreview AERA journals from 2009 to 2019. We found that two thirds of articles used at least one racial category term, with an increase from about half to almost three quarters of published studies between 2009 and 2019. Other trends include the increasing popularity of the term Black, the emergence of gender-expansive terms such as Latinx, the popularity of the term Hispanic in quantitative studies, and the paucity of studies with terms connoting missing race data or including terms describing Indigenous and multiracial peoples.